2021
DOI: 10.1186/s43141-020-00104-z
|View full text |Cite|
|
Sign up to set email alerts
|

New insights on key genes involved in drought stress response of barley: gene networks reconstruction, hub, and promoter analysis

Abstract: Background Barley (Hordeum vulgare L.) is one of the most important cereals worldwide. Although this crop is drought-tolerant, water deficiency negatively affects its growth and production. To detect key genes involved in drought tolerance in barley, a reconstruction of the related gene network and discovery of the hub genes would help. Here, drought-responsive genes in barley were collected through analysis of the available microarray datasets (− 5 ≥ Fold change ≥ 5, adjusted p value ≤ 0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…In Chickpea ( Cicer arietinum L.), 15 genes were down-regulated in roots and 10 genes were down-regulated in stems under abiotic stress [ 59 ]. The OsWRKY55 negatively regulates drought tolerance in transgenic rice lines [ 60 ], The transcription level of HvWRKY42 increased in Barley ( Hordeum vulgare L.) under drought stress, which indicated that HvWRKY42 was regulating the drought adaptability of barley [ 61 ]. The HvWRKY3 showed 13 fold high expression and 4 genes showed 2-fold high expression under drought stress [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Chickpea ( Cicer arietinum L.), 15 genes were down-regulated in roots and 10 genes were down-regulated in stems under abiotic stress [ 59 ]. The OsWRKY55 negatively regulates drought tolerance in transgenic rice lines [ 60 ], The transcription level of HvWRKY42 increased in Barley ( Hordeum vulgare L.) under drought stress, which indicated that HvWRKY42 was regulating the drought adaptability of barley [ 61 ]. The HvWRKY3 showed 13 fold high expression and 4 genes showed 2-fold high expression under drought stress [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…To manage stress conditions, many molecular changes can take place by activating and regulating certain stress-related genes [39]. Identifying important and differentially expressed genes in response to stress environments might be a suitable approach toward a better understanding of stress responses and their mechanisms [23]. Past studies indicated that rice MYB59 is positively regulated with drought [46] and there are little studies about the regulation of OsMYB transcripts under K + and NO 3 − stress.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, studies on cis -regulatory elements (CREs) provide a foundation for future experiments 54 , 72 , 73 . Regulatory elements play a crucial role in plant responses to various stresses, including drought stress 74 . There are not many studies comparing promoters of different types of MTs in one plant species 64 , 65 , 72 .…”
Section: Resultsmentioning
confidence: 99%